Electrocardiogram Characteristics of Chronic Obstructive Pulmonary Disease Patients are Associated with Severity and Disease Duration - Ni Made Elva Mayasari; Kristinawati Kristinawati; Rara Krisdayanti; Lisa Permata Sari (Universitas Islam Bandung, 2022)
Chronic obstructive pulmonary disease (COPD) is characterized by persistent airflow limitations associated with an increase in chronic inflammatory responses to the airways and lungs. COPD patients are more likely to be hospitalized and die from cardiovascular disease. This study aims to determine the factors associated with the incidence of electrocardiogram (ECG) abnormalities in COPD patients. This a cross-sectional study with an analytical observational design. From October 30 to December 5, 2019, data was collected on 42 COPD patients, inpatients, and outpatients at Muhammadiyah Palembang Hospital who met the inclusion and exclusion criteria. A questionnaire was used to collect data, and spirometry and an electrocardiogram test were used to measure pulmonary function and detect ECG abnormalities. Research variables included age, sex, smoking habits, severity, and duration of COPD. Data analysis using the chi-square test and followed by a logistic regression test found a significant relationship between severe to very severe COPD and ≥5 years of suffering from COPD with the incidence of ECG abnormality (p<0.05). The severity and the length of time of suffering from COPD are significantly related to the incidence of ECG abnormalities in outpatients and inpatients.